Impact of length of cryopreservation and origin of cord blood units on hematologic recovery following cord blood transplantation - 栗田 尚樹; 千葉 滋; Kurita Naoki; Frassoni Francesco; Chiba Shigeru; Podestà Marina (Bone marrow transplantation, 2015)
As the history of the cord blood banking system has lengthened, the number of cord blood units (CBUs) cryopreserved for years has increased. The global expansion of cord blood banking resulted in active international exchange of CBUs. To determine whether long-term cryopreservation and international shipment of CBUs affect the quality of the units and outcome after transplantation, we retrospectively analyzed the quality of 95 CBUs and the hematologic recovery of 127 patients with hematological malignancy following single-unit cord blood transplantation. Of the 127 CBUs used to transplant, 42 units were cryopreserved for long periods (5–11.8 years), and 44 units were shipped from distant countries. We found that length of cryopreservation and origin of CBUs did not affect the ratio of viable total-nucleated cells after thawing. Also, neutrophil engraftment was not affected by long-term cryopreservation (> 5 years) or origin (from distant countries), (hazard ratio, 0.91 and 1.2; P=0.65 and 0.41; respectively). The number of CD34+ cells before freezing (> 1.4 cells/kg recipient) was the only factor that enhanced neutrophil engraftment (hazard ratio, 1.8; P<0.01). This suggests that length of cryopreservation and origin need not be prioritized over the CD34+ cell dose when selecting CBUs.